Acylated Ghrelin Receptor Agonist HM01 Decreases Lean Body and Muscle Mass, but Unacylated Ghrelin Protects against Redox-Dependent Sarcopenia - Rojina Ranjit; Holly Van Remmen; Bumsoo Ahn (MDPI AG, 2022)
Sarcopenia, the progressive loss of muscle mass and dysfunction, universally affects the elderly and is closely associated with frailty and reduced quality of life. Despite the inevitable consequences of sarcopenia and its relevance to healthspan, no pharmacological therapies are currently available. Ghrelin is a gut-released hormone that increases appetite and body weight upon acylation, which activates its receptor GHSR1a. Recent studies have demonstrated that acyl and unacylated ghrelin are protective against acute pathological conditions of skeletal muscle. We hypothesized that both acyl ghrelin receptor agonist (HM01) and unacylated ghrelin ameliorate muscle atrophy and contractile dysfunction in oxidative stress-induced sarcopenia. HM01, unacylated ghrelin, or saline was delivered via osmotic pump. HM01 increased food consumption transiently, while the body weight remained elevated. It also decreased lean body mass and muscle mass of wildtype and Sod1KO. In contrast, unacylated ghrelin ameliorated loss of muscle mass by 15-30% in Sod1KO mice without changes in food consumption or body weights. Contractile force was decreased by ~30% in Sod1KO mice, but unacylated ghrelin prevented the force deficit by ~80%. We identified downregulation of transcription factor FoxO3a and its downstream E3 ligase MuRF1 by unacylated ghrelin. Our data show a direct role of unacylated ghrelin in redox-dependent sarcopenia independent of changes of food consumption or body weight.